Experiment and dynamic simulation study on propane pre-cooling double nitrogen-expander liquefaction process for medium-pilot LNG plant. (April 2020) - Zhu, Jianlu; Zhang, Wei; Liu, Shengnan; Li, Yuxing; Liu, Miaoer; Yin, Quanshen; Xie, Bin; Yu, Xichong; Li, Yan
Highlights: A simplified dynamic simulation model of plate-fin heat exchanger was established. The consistency of dynamic simulation and experimental operation data was verified. The response of the process under disturbances and accident conditions was simulated. Abstract: In the field of LNG simulation study, most optimization studies have concentrated on the LNG processes at steady-state simulation, and only a few studies have reported the dynamic simulation of the LNG process, which is closer to actual operating conditions. The main purpose of this study was to design a dynamic model of propane pre-cooling double nitrogen-expander LNG process based on an actual LNG plant, to investigate the dynamic behavior of this process, which had been considered suitable for FLNG process in previous studies. Furthermore, this is one of the first studies to verify the dynamic simulation of this process through the actual operation of an LNG plant. First, the dynamic models of the main equipment used in this process were developed. Second, a dynamic simulation of this process was performed, and the dynamic behaviour was investigated. Finally, to verify the accuracy of the dynamic simulation, different types of dynamic conditions were added to the simulation to investigate the behaviour of the process, including disturbances in the feed gas flow rate and shutting down of the propane system. Further, the dynamic responses and average errors between the experimental and simulated values were obtained and discussed. The results indicated that the two-stream heat exchange model can be used to replace the multi-stream heat exchange model for dynamic simulation, with the average error of dynamic simulation being under 10%, the control system can resolve the problem of excess cooling capacity and make the entire system run stably in the case of feed gas flow rate disturbance, the whole system returns to stability within 100 min in the case of the propane system shutdown. The results can provide feasible prediction and verification methods for the construction of large experimental and liquefaction production devices in the future.